Lugares de memória: Jesuíno Brilhante e os testemunhos do Cangaço nos Sertões do Oeste Potiguar e fronteira paraibana - Holanda, Lúcia Maria de Souza (2010)
This dissertation examines the role of Jesuino Brilhante at Cangaço and his possible place in the memory" representing a past that is so present in the social memory through the geography of representations. For such, we will approach this issue from an interpretive point of view, in reference to the passage of Cangaço trough the backwoods of Rio Grande do Norte and Paraíba. The contention that permeates this study is that which states that memory; imagination and representation are inextricably linked to the social-space production process. We seek a theorical approximation between the concepts of place-world, territory, memory, imagination and the social representations; we live in, exercising an interdisciplinary dialogue which maintains, however, a geographical bias peculiarity. Geography has scarcely explored the role of the imaginary component relating to socio-environmental and socio-spatial relations. The symbolism found in worldviews and the social imaginary are also components of geographical space. Some symbolic interpretations have, a certain spatial space, thereby giving it opportunity to appear to up till today. Oral history, memory, imagination and representations, were organized and expressed using the multiplicity of languages, within the history of the outlaw Jesuíno Brilhante. Thus, in regard to methodological aspects, Oral History and the Social Imaginary provided information that enabled us to understand better the feelings inherent to the social representations that have permeated the focus of the research. We could observe the appearance of beliefs, fantasies, reasoning, speculations and intuitions within the sanctioned system: a range of foundational elements that resulted from the activities of reasoning and imagination thus constituting the process of symbolization and the myth of this outlaw. This way, the Geography of Social Representations and the Social Imaginary denote a fragment of reality as an amalgamation, establishing a set of cultural and historical interpretations as well as collectively constructed experiences. We believe that the topic presented deserves more reflection, but we expect this work would strengthen the relevance of conducting research about the human beings in their plenitude, thereby, giving vocal opportunity to a diversity of previously marginalized social actors. As far as both cultural geography and oral history are concerned, we might have the opportunity to hear sacred, poetic, folkloric and mythical voices, the voices of reason and feeling, and the voices of human beings in their plenitude.